A two-decade Review of Medical Ethics in Iran - F Zahedi; SH Emami Razavi; B Larijani (Tehran University of Medical Sciences, 2009)
"nThe growing developments in science and technology have raised ethical challenges which should practically be addressed by scientists, regulatory bodies and policy makers. Likewise, challenging issues of medical ethics have also drawn a great deal of academic attention in Iran. In other words, recent decades have been an occasion of considerable development for contemporary bioethics in Iran. At first, the ongoing initiatives to arrange the national and regional research ethics committees and to compile the national strategic plan for medical ethics is worth mentioning. Currently, research ethics committees are actively established in the universities and research centers across the country. Furthermore, the subject of ethics in different fields of science, which was followed in a traditional approach previously, is an important object of discussion currently. Much research is now being undertaken in various areas of bioethics nationwide. Consequently, during the period under review, considerable articles and books have been published in the emerging subjects of bioethics. Several educational workshops and courses have been frequently taken place in the universities and research centers. Foundation of academic courses and fellowship in bioethics are also among the recent activities in the realm of medical ethics education in Iran. Likewise, considering several areas of bioethics that need legislation or reconsideration of previous regulations; the authorities, policy-makers, and scientists have carried out some endeavors to prepare appropriate law, codes, and guidelines. This report summarizes the bioethical activities and achievements in different fields of policy-making, organizing, teaching, and putting ethics into practice in our country during two recent decades.